Teaching High School Cultural Studies in the Age of Trump - Cashmere, DJ (Radical Teacher, 2018)
In the fall of 2016, I began my third year teaching Cultural Studies Seminar at Chicago Bulls College Prep (CBCP), where I’d been working as a teacher since 2010. CBCP is a campus of the Noble Network of Charter Schools and is located on Chicago’s Near West Side. The school serves a population of students that is roughly 2/3 Latino and 1/3 African American, and about 90% of CBCP’s students receive free or reduced-price lunch. Every year, 100% of seniors are accepted to college. I had first devised the course in the fall of 2014, when my principal and assistant principal gave me permission to re-focus the 11th-grade literacy class I was teaching. I wanted to specifically study racism, classism, sexism, and heterosexism in America, with an eye toward how those systems operate and how they can be—and have been—resisted. We put our heads together and came up with the name “Cultural Studies Seminar.” The essay describes teaching the course during the semester of the 2016 U.S. Presidential election.